Islam and terrorism: beyond the wisdom of the secularist paradigm - El-Mesawi, Mohamed El-Tahir; Khriji, Tesnim (IIUM Press, 2006)
Since the end of the Cold War, the West has mounted a campaign against Islam as the essential source of terrorism and the Muslims as necessarily terrorists. However, the problems of violence and terror are not isolated issues but have epistemological and unspoken real causes. Violence is related to despotism, especially the despotism of hegemony. The US-led war on terrorism is not a simple struggle between good and evil. The hidden reasons behind it makes it difficult for the Muslims and others in the Third World to appreciate the efforts.